2011
DOI: 10.1200/jco.2011.29.4_suppl.253
|View full text |Cite
|
Sign up to set email alerts
|

An interim analysis of a phase II study of the combination of TACE and sorafenib in patients with unresectable hepatocellular carcinoma in National Cancer Center Korea (COTSUN KOREA, NCT00919009).

Abstract: 253 Background: Transarterial chemoembolization (TACE) is the palliative treatment for patients with unresectable HCC. TACE-induced ischemic injury is known to increase circulating VEGF and related with poor prognosis.The aim of this study is to evaluate efficacy and safety of combined TACE with sorafenib, VEGFR inhibitor in unresectable HCC patients. Methods: This study is a non-randomized, open-labeld, single-arm, phase II investigator-initiated clinical study. Estimated number of subjects was 50 under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For example, switch to sorafenib might be a reasonable measure in patients with intermediate‐stage HCC who are not eligible for, or progressed after TACE 16 . The combination of TACE plus sorafenib might also be a suitable alternative to protect against tumor progression due to ischemic injury following TACE; 17–19 this strategy is supported by recent preliminary results of a prospective study which reported prolonged TTP 20 . The need for evaluation of the outcome of combined TACE and systemic therapy in HCC patients has recently been given high priority 21 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, switch to sorafenib might be a reasonable measure in patients with intermediate‐stage HCC who are not eligible for, or progressed after TACE 16 . The combination of TACE plus sorafenib might also be a suitable alternative to protect against tumor progression due to ischemic injury following TACE; 17–19 this strategy is supported by recent preliminary results of a prospective study which reported prolonged TTP 20 . The need for evaluation of the outcome of combined TACE and systemic therapy in HCC patients has recently been given high priority 21 …”
Section: Discussionmentioning
confidence: 97%
“…16 The combination of TACE plus sorafenib might also be a suitable alternative to protect against tumor progression due to ischemic injury following TACE; [17][18][19] this strategy is supported by recent preliminary results of a prospective study which reported prolonged TTP. 20 The need for evaluation of the outcome of combined TACE and systemic therapy in HCC patients has recently been given high priority. 21 The aim of this study was to identify factors associated with TACE refractoriness.…”
Section: Discussionmentioning
confidence: 99%
“…The median TTP was 6 months. A phase II study of the combination of TACE and sorafenib in patients with unresectable HCC showed that the median TTP was 5.1 months [ 19 ]. Hu et al compared TACE plus sorafenib with TACE alone in Barcelona Clinic Liver Cancer stage C patients, and the TTP was longer in the combined group (2.6 months vs .…”
Section: Discussionmentioning
confidence: 99%